A Study on the Understanding and Treatment of Dizziness based on Theories Related to the Yellow Emperor Internal Classic - Wang, Changjing; Zhang, Jinpei (Journal of Contemporary Medical Practice, 2025)
This article reviews the understanding and treatment in the field of dizziness based on the theoretical knowledge related to the Yellow Emperor Internal Classic, introduces the etiology of dizziness as well as the dialectical thinking, and summarizes the diverse views of ancient and modern medical practitioners. This paper aims to provide reference for doctors in the field of dizziness and to suggest some ideas and suggestions for follow-up research.